Metal ions bound to the human milk immunoglobulin A: Metalloproteomic approach - Costa Pozzi, Carla Mariane [UNESP]; Braga, Camila Pereira [UNESP]; Souza Vieira, Jose Cavalcante [UNESP]; Cavecci, Bruna [UNESP]; Queiroz, Joao Vitor de [UNESP]; Barbosa, Herbert de Souza; Zezzi Arruda, Marco Aurelio; Gozzo, Fabio Cesar; Padilha, Pedro de Magalhaes [UNESP] (Elsevier B.V., 2015)
The presence of calcium, iron, and zinc bound to human milk secretory IgA (sIgA) was investigated. The sIgA components were first separated by two-dimensional polyacrylamide gel electrophoresis and then identified by electrospray ionization-tandem mass spectrometry (ESI MS MS). The metal ions were detected by flame atomic absorption spectrometry after acid mineralization of the spots. The results showed eight protein spots corresponding to the IgA heavy chain constant region. Another spot was identified as the transmembrane secretory component. Calcium was bound to both the transmembrane component and the heavy chain constant region, while zinc was bound to the heavy chain constant region and iron was not bound with the identified proteins. The association of a metal ion with a protein is important for a number of reasons, and therefore, the findings of the present study may lead to a better understanding of the mechanisms of action and of additional roles that sIgA and its components play in human milk. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Flame atomic absorption spectrometry; Human milk; Electrospray ionization-tandem mass; spectrometry; Metalloproteomics; Secretory IgA; Two-dimensional electrophoresis